HUBUNGAN POLA KOMUNIKASI INTERPERNONAL DALAM KELUARGA DAN INTERAKSI SOSIAL TERHADAP KENAKALAN SISWA SMA SWASTA DI KOTA PADANGSIDIMPUAN - Rafiq, Mohd. (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis research represent research of field with aim to see communications pattern [relation/link] of interpersonal in social interaction and family [of] adolescent group with mischief of student of SMA Private sector [in] Town of Padangsidimpuan. This Research pertained quantitative research, with approach of correlational, namely research trying to connect or look for [relation/link] [among/between] one variable with other variable This Research population [is] entire/all SMA Private sector exist in Town of Padangsidimpuan. From the population above, taken five schools of Private SMA sector by using technique of Simple Random Sampling, [is] so that made [by] sample in this research. As for five the school [is] SMA Nurul Ilmi, SMA Perguruan Rakyat, SMA Abdi Negara, SMA Karya Baru and SMA Panca Dharma. Data obtained analyzed by using SPSS. The result use statistic and analysis of correlational moment product stemming from Karl Pearson. Result of Examination of hypothesis indicate that communications pattern of interpersonal in family have [relation/link] which [is] significant with mis-behaviour of student.Kata Kunci: Komunikasi Interpersonal, Keluarga, Remaja